Development of basic quantity surveying learning module through 21st century learning activity - Abd Hafidz, Annis Surraiyya; Mohamad, Mimi Mohaffyza (2021)
Technical and Vocational Education in Malaysia (TVET) is one of the most important branches of education to produce a balanced human capital. Not only the skills in the field need to be emphasized, but the skills also need to be enhanced under the 'Eleventh Malaysia Plan ' (RMK-11). 21st century learning is a student centered learning process based on 4C’s elements which are communication, collaborative, critical thinking and creativity. The importance of producing 21st century learning based modules is essential to ensure that TVET students, especially at the Vocational College, are exposed to 21st century learning activities and can apply the 4C’s element. Therefore, this study was conducted to develop Basic Quantity Surveying Learning Module Through The 21st Century Learning Activity that tested its validity and credibility as reference material or teaching aids to assist teachers and students taking this course. This module design has two stages beginning with goal building and ending with a complete module that is ready to use. The module validation process involves using the instrument and involving three experts for verification. The evaluation of the module validation consists of a questionnaire consisting of 28 items based on the format and content of the module. The findings show that Basic Quantity Surveying Learning Module Through The 21st Century Learning Activity is highly validated. Analyst views are presented as a percentage. Based on the result, 96% agree on the design of the module while 98.46%. agree on the content of the module developed. Through the analysis of the findings, the Basic Quantity Surveying Module Through The 21st Century Learning Activities has high content validity.